Elaboración de papillas a base de plátanoo (Musa paradisiaca L) variedad capirona, arroz (Oryza sativa) y camu camu (Myrciaria dubia), para niños (<5 años) - Rios Arevalo, Jhonatan Eduardo Paul (2021)
In this research carried out entirely at the facilities of the FIA – UNAP pilot plant, chemical physical analyses of the raw materials (banana variety capirona, silk, camu camu, instant rice) were first performed, obtaining very reliable results that do not differ greatly by having standard deviations less than one, then 6 formulations were made, trying to balance the nutritional part, according to the requirements of children of age (< 5 years), followed by followed by followed by followed by I perform the technological tests of the processing (at this stage of processing to obtain the porridge, the temperature of the heat treatment was 120ºC for 20 minutes), using the aforementioned raw materials, but already in pulps and instant flours as is the case of rice. Once processed, chemical physical analyses such as: moisture determination, ash, fats, proteins, carbohydrates, calories, pH (20ºC), titrated acidity, vitamin C, soluble solids and dry matter, as well as mineral analyses (calcium, phosphorus, iron and potassium), then microbiological tests were carried out (Mesophile aerobios, Escherichia coli and Salmonella sp.), leaving them suitable for human consumption, within the quality range accepted by MINSA/DIGESA, the organoleptic evaluation was the carried out by 25 untrained taster being (formulation F3 using the two varieties of banana capirona and silk were the chosen ones). Already in the last stage of the evaluations were carried out acceptability tests by the children of the garden Nº 60898, of Nina Rum, located in the populated center of Zungarococha, district of San Juan, Province Maynas, in the Department of Loreto, where they confirm that the formulation F3, of porridge with capirona banana is the one with the greatest acceptability.